Development of non‐governmental organisation‐academic partnership to tackle rabies in Africa and Asia. (8th October 2018) - Gamble, L.; Gibson, A.; Mazeri, S.; de C Bronsvoort, B. M.; Handel, I.; Mellanby, R. J.
Abstract : Rabies kills approximately 60, 000 people each year, mainly in sub‐Saharan Africa and Asia, of which 40% of victims are less than 15 years old. Once clinical signs develop, the disease is almost invariably fatal. Globally, rabies has been estimated to cause 3∙7 million disability‐adjusted life years and $8∙6B in economic losses annually. The vast majority of human rabies cases are caused by bites from rabies‐infected dogs. Despite this loss of human life and resultant economic and societal costs, rabies can be prevented in both humans and dogs by vaccination. This has been demonstrated in many countries, notably in Central and South America, where large‐scale, high coverage mass dog vaccination programmes have dramatically reduced the incidence of rabies. Even in parts of Africa and Asia, projects have shown that rabies can be eliminated locally. Nevertheless, rabies remains an important cause of mortality in many sub‐Saharan and Asian countries. The reasons why some countries have been able to effectively eliminate rabies whereas others have not are complex and often impossible to definitively identify; commonly cited explanations include political, economic, logistical and societal barriers.